Kariotypes of fetus based on screening of biochemical markers in the blood serum of pregnant women of the risk group (Experimental biology, 2017)
The article presents the data on of prenatal diagnosis of biochemical screening and cytogenetic examinations in 2015-2016. According to the results of biochemical screening, the mother's age factor, ultrasound examination, congenital malformation in the family history, etc.,1800 pregnant women were referred to invasive diagnostics. Cytogenetic studies of the fetus were conducted including 1240 (68,9%)  pregnant women. Of these, in karyotypes of 84 fetuses, chromosomal abnormalities were detected, which composed 7.8%. In 2015, according to the results of 607 invasive diagnostics in 43 fetuses (7.1%), and in 2016 - out of 633 invasive diagnoses in 41 fetuses (6,5%), deviations of the karyotype were determined. In 81 (96.4%) cases, numerical disorders were observed, of them in 6 (7.1%) cases - violations in the system of sex chromosomes. In 3 (3.6%) cases structural abnormalities of chromosomes were noted. In 13 (13.4%) of the fetuses, neural tube development defects were detected. In 2015, taking into account the age factor, in pregnant women under 35 years, abnormalities of the karyotype of the fetus reached 51.9%, and at the age of 35 years - 48.1%, and in 2016 – 66,6% and 33,3%, respectively. An increase in the frequency of karyotypic fetal dysfunction is fixed to be 1,1 times in 2015 and 2,0 times in 2016.
Keywords: protein РАРР-А; hormone β-hCG; protein AFP; hormone free estriol; biochemical research; prenatal diagnosis; fetal karyotype